Corporate blogging: Medarbejderes kommunikative handlekraft - Tanja Juul Christiansen (Copenhagen Business School (CBS), 2010)
– Organizational identity has traditionally been understood as a fixed product that can be identified and communicated to employees. Organizational identity formation should, however, be understood as a reflexive process. There is not just one organizational identity but several, and the construction of these identities takes place in a continuing process among several participants. Yet, in many organizations management aims at a conventional identity formation in the official internal identity communication, when communicating identity to employees with the ambition of creating a monolithic organization of devoted employees. This kind of conventional identity formation has several implications. Firstly, it creates a gap between the official and the unofficial identity formation. Secondly, it runs the risk of making the organization appear untrustworthy. Thirdly, it may lead to a homogenous work force, which seems contradictory to the strive for innovation and creativeness that also characterizes contemporary organizations. Finally, its inherent aim of social control seems morally questionable. Thus, organizations could beneficially strive for a higher degree of reflexiveness by letting more voices be part of the official identity formation. The empirically-based research on how to facilitate such reflexivity is, however, sparse. In order to address this gap in the literature, this PhD dissertation explores how to affect rhetorical agency at work by implementing internal employee blogs in organizations....
hdl:10398/8173
Keywords: 650